Peran Modal Sosial dalam Pengembangan Wisata Berkelanjutan: Studi Kasus di Kawasan Wisata Lumbung Stroberi-Kota Batu - Windiani; Lienggar Rahadiantino; Eka Dian Savitri; Endang Susilowati (Jurnal Sosial Humaniora, 2022)
With Pandanrejo Tourism Village in Bumiaji District, Batu City serving asthe focal point of this investigation, the study's overarching objective is toascertain what part social capital plays in the process of transformingLumbung Stroberi into a sustainable tourism destination. The concepts ofsocial capital, collaboration, and sustainable development are investigatedthrough the lens of this study, which employs qualitative research methodsand a participatory rural appraisal approach to research. Observations ofparticipants and conversations within focus groups are going to be used tocollect data. Informants for this study came from local stakeholders whowere active in the development of Lumbung Stroberi tourism in Pandanrejovillage, which is located in Batu City. The results of this research make asignificant contribution to the development of laboratory-based science, inparticular the sociology of development. In order to foster more sustainabletourism and community development in Indonesia, local governments andother stakeholders can make use of the practical benefits provided byresearch.